2018
DOI: 10.1080/20009666.2018.1450592
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of invasive mechanical ventilation in hospitalized patients with sepsis: data from National Inpatient Sample

Abstract: Background: Sepsis is a significant cause of mechanical ventilation in hospitalized patients.Objective: The aim of our study was to recognize the demographic and clinical characteristics associated with an increased need for invasive mechanical ventilation in hospitalized sepsis patients.Methods: We used National Inpatient Sample database from the years 2009–2011 to identify sepsis patients requiring invasive mechanical ventilation. We compared demographic and clinical characteristics of sepsis patients requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Nevertheless, the mortality for patients with COVID-19 requiring IMV is worse than most common medical conditions requiring ICU admission. The reported ICU mortality from sepsis is 40% [ 33 ], severe COPD 30% [ 34 ] and pancreatitis 25% [ 35 ], all lower than COVID-19 patients requiring IMV in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, the mortality for patients with COVID-19 requiring IMV is worse than most common medical conditions requiring ICU admission. The reported ICU mortality from sepsis is 40% [ 33 ], severe COPD 30% [ 34 ] and pancreatitis 25% [ 35 ], all lower than COVID-19 patients requiring IMV in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Sepsis, defined as a life-threatening organ dysfunction due to a dysregulated immune response to infection, affects millions of patients per year and carries a high risk of mortality, becoming a major global health problem ( 1 , 2 ). According to the Global Burden of Diseases Study, in 2017, an estimated 48.9 million incident cases of sepsis were reported worldwide with nearly 11.0 million patients dying, accounting for 19.7% of all global deaths ( 3 ).On the other hand, sepsis is often complicated with acute respiratory distress syndrome that requires mechanical ventilatory support ( 4 , 5 ), research showed that more than 20% of septic patients needed invasive ventilation in the USA ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent reports, approximately 21% of septic patients required mechanical ventilation in the United States ( Rashmi et al, 2018 ). As we all know, patients with prolonged mechanical ventilation suffer from higher mortality and hospital costs ( Goligher Ewan et al, 2018 ; Louise, 2020 ).…”
Section: Introductionmentioning
confidence: 99%